“The Negative Capability of Camouflage”: Fleeing Diaspora in Fred Wah’s Diamond Grill - Sugars, Cynthia (Studies in Canadian Literature, 2001)
If an articulation of diasporic identity threatens to embroil one in a reductive essentialism, a number of recent writers and theorists have attempted to deconstruct this delimiting configuration by applying a non-paradoxical vision of resistance and reconciliation to the diasporic experience itself. Fred Wah’s Diamond Grill is one such text, striving to articulate a non-paradoxical vision of identity and evade the restricting designations of a narrow-identity politics. Wah effects a "de-diasporization" by which the traditional colonialist insistence on spatializing other worlds is reclaimed in the postcolonial emphasis on that space as the locus of newly asserted and shifting hybridized identities. This de-diasporization is undertaken in three ways: through the mixed ancestral inscriptions on the "diasporic body," through the narrator’s ontological introjections of Canada as it was experienced by his displaced ancestors, and through the de-ontologized locale of the Diamond Grill itself. Wah shows how diasporic locations can be viewed as sites of radical reorientation — of language, subjectivity, emplacement, identity, and inheritance.